FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STIGMA GURU TERHADAP ANAK HIV POSITIF (Studi pada Guru di Sekolah Mitra PKBI Daerah Jawa Tengah dalam Implementasi Pendidikan Kesehatan Reproduksi dan Seksual) - Rizal Imam Muksin; Zahroh Shaluhiyan; Bagoes Widjanarko (Jurnal Kesehatan Masyarakat (Undip), 2015)
The problem of HIV and AIDS is not only related to health problems, but the problems are the impact of social issues such as stigma and discrimination against people living with HIV from an adult or a child. In 2012 children aged 0-19 years with AIDS in Indonesia there are 1,410 children, and in Central Java, there are 176 children with AIDS. Being right of every child to education in schools including the children with HIV positive. The purpose of this study is to determine some factors that associated with stigma of teachers to children with HIV.This research is cross-sectional descriptive study with comparative study method that used a sample teachers consist of 25 teacher’s partner and 25 teachers is not partner in 5 schools that become partners of the IPPA Central Java region in the implementation of sexual and reproductive health education in schools.The results of these studies found that variables associated with the stigma of the children with HIV are Sex (Gender), the number of educational materials, knowledge about HIV AIDS, perception about friends attitude, and perception about the school principal attitude.